Analysis of Critical Discussion in The Article "Different Fate: THR Civil Servants In This Week, THR of Livers Postponed and Installed" (Kompas, 11 Mei 2020) - Huda, Muhammad Misbahul (QAULAN: Journal of Islamic Communication, 2020)
Abstract: The focus of this research is (a) describing the dimensions of the text, (b) describing discursive practices, (c) describing socio-cultural praxis, and assumptions of social irregularities through obstacles and how to overcome these obstacles, based on Kompas 11 May 2020 Edition. with the title "Difference in Fate: THR PNS Liquided This Week, THR Labor Delayed and Installed. This type of research uses library research, while data collection uses documentation, and Norman Fairclough's Critical Discourse Analysis (AWK) as a tool for analysis. Based on the research, the following results were obtained: (a) the dimensions of the text. The text in the Kompas report seems to speak of a clear caste difference between civil servants and workers. (b) dimensions of discursive practice. Besides the existence of Covid-19, Circular Letter about the THR of workers that can be postponed or paid in installments and the news about the THR PNS immediately disbursed, explicitly indicates that there are social irregularities that occur. (c) socio-cultural praxis dimensions. With this news, it triggers the reaction of the workers / laborers to launch a demonstration, either through the leadership of workers throughout Indonesia or even there will be a demonstration going down. While the assumptions of social irregularities can be seen in the inequality and discrimination of workers / laborers caused by the government. The government seems to favor the civil servants and company owners. This can be prevented by ensuring that the THR of workers is controlled up to the hands of the workers, and that the Circular Letter will instead be used as a weapon for company owners so that they do not meet the workers' THR, this requires the supervision of the government.